Association of programmed cell death ligand 1 and circulating lymphocytes with risk of venous thromboembolism in patients with glioma. Issue 3 (17th May 2020) - Mir Seyed Nazari, Pegah; Berghoff, Anna S; Preusser, Matthias; Moik, Florian; Posch, Florian; Ricken, Gerda; Riedl, Julia; Hell, Lena; Marosi, Christine; Hainfellner, Johannes A; Pabinger, Ingrid; Ay, Cihan
Abstract : Introduction: The role of the adaptive immune system in the pathophysiology of cancer-associated venous thromboembolism (VTE) has not been investigated in detail. Programmed cell death ligand 1 (PD-L1) is an immune checkpoint molecule responsible for immune evasion in several cancer entities, as expression on tumour cells silences the T cell-mediated immune response. Given the interrelation between inflammation, haemostasis and cancer, we aimed to investigate the association of players of the adaptive immunity (eg, lymphocytes, tumour PD-L1) with risk of VTE in patients with glioma, one of the most prothrombotic cancer types. Methods: In this prospective observational single-centre cohort study, patients with newly diagnosed glioma or regrowth after resection were included. Primary endpoint was objectively confirmed VTE. At study inclusion, a blood draw was performed. Tumour PD-L1 expression was assessed via immunohistochemistry. Results: In total, 193 patients were included. PD-L1 expression in ≥1% of tumour cells was observed in 20/193 (10.4%) glioma. In multivariable cox-regression analysis, on adjustment for age, sex and WHO grade IV, systemic lymphocyte counts were significantly associated with risk of VTE (HR per 1 G/L increase (95% CI): 1.15 (1.03 to 1.29), p=0.013). In contrast, no significant difference in risk of VTE was found regarding the PD-L1 status: the cumulative 24 months probability of VTE was 17.0% in patients with no PD-L1 and 11.8% in those with PD-L1 expressing tumours (p=0.663). Conclusion: In summary, PD-L1 expression was not associated with risk of VTE. Interestingly, peripheral lymphocytes, which are key players in adaptive immunity, were linked to an increased risk of glioma-associated VTE.